Ownership structure and firm risk : evidence from China : a thesis presented in fulfilment of the requirement for the degree of Doctor of Philosophy in Finance at Massey University, Manawatu campus, New Zealand - Xie, Feng (Massey University, 2018)
This thesis investigates the effects of ownership structure on firm risk in China. The first essay of this thesis provides an overview of the Chinese privatisation programmes that profoundly shapes the ownership structure of Chinese listed firms, and it reviews and discusses the corporate governance and firm outcomes resulting from the privatisation programmes in China. In particular, it presents a detailed survey of China’s privatisation programmes from its Share Issue Privatisation (SIP) to the Non-tradable Share (NTS) reform, Overall, it reveals that the SIP has achieved limited success in China, which is mainly due to the partial trading policy and partial privatisation characteristics, while the NTS reform yields greater improvements of governance mechanisms and outcomes. This thesis then, examines the impact of ownership structure on firm risk in privatised firms. Essay two examines the effect of residual state ownership on stock return volatility following the NTS reform. The empirical evidence shows that residual state ownership mitigates the stock return volatility. It indicates that state ownership retention in the aftermath of sudden privatisation reform can signal the government willingness to bear the firm risk. The mitigating effect is especially pronounced in firms controlled by the government agents. Furthermore, firms with higher government ownership reduce stock return volatility through implementing more conservative corporate policies. However, the volatility-mitigating effect appears to be temporary, lasting only for three years after state shares become fully tradable. Essay three investigates the relationship between the shareholdings of the Qualified Foreign Institutional Investors (QFIIs) and stock price crash risk. This essay adopts a governance mechanism, threat of exit, to examine the role of QFIIs on stock price crash risk. The evidence shows that long investment horizon and existence of multiple QFIIs exert credible exit threat to discipline management, and in turn, reduce stock price crash risk. Further, it shows that the corporate site visits of portfolio firms by QFIIs is a channel through which the credible exit threat works effectively.
Essay one was published as Xie, F., Chi, J., & Liao, J. (2016.) From share issue privatisation to non-tradable share reform : A review of privatisation in China. Asian-Pacific Economic Literature, 30(2), 90-104. https://doi.org/10.1111/apel.12149 A revised version of Essay two was published as Xie, F., Anderson, H.D., Chi, J., & Liao, J. (2019.) Does residual state ownership increase stock return volatility? Evidence from China's secondary privatization. Journal of Banking and Finance, 100, 234-251. https://doi.org/10.1016/j.jbankfin.2019.01.012
Keywords: Stock ownership; China; Corporate governance; Corporations; Valuation; Privatisation